Spontaneous Human Myometrial Contractility in the Third Trimester of Pregnancy in Relation to Past Mode of Delivery - Ryan, Gillian A.; Nicholson, Sarah M.; Crankshaw, Denis J.; Morrison, John J. (American Journal of Perinatology, 2019)
Objective It is well established that women with a previous vaginal delivery have higher success rates in relation to vaginal birth after cesarean than those without. The aim of this study was to examine the effect of past mode of delivery on contractile parameters of human myometrium in vitro.Study Design Myometrial strips were excised from 64 women at cesarean delivery (CD) and recordings of spontaneous contractile activity analyzed and compared across three clinical groups: (1) women with no previous delivery (Group 1); (2) women with CD only (Group 2); and (3) women with a history of vaginal delivery and CD (Group 3).Results Myometrial samples from women in Group 3, women who had a previous vaginal delivery, had a significantly greater maximum amplitude of contractions (p < 0.05), a greater force (mean contractile force) of contractions (p < 0.01), and a faster rate of rise (p < 0.01) and relaxation of contractions (p < 0.05) than those in Groups 1 and 2.Conclusion Many of the functional parameters of human uterine contractions are altered, or enhanced, in the women who have had a previous vaginal delivery, when compared with those without. This may partly explain the clinical differences observed in labor.
Keywords: myometrial contractility; labor; vaginal birth after cesarean